Analisis Faktor Sosial Penyebab Ketidakpatuhan Mahasantri di Pesantren Salaf-Inklusif: Implikasi untuk Pengelolaan Kebijakan Pendidikan Islam - Maryanto, Lilik; Choer, Muhammad Masduki Ali; Lessy, Zulkipli (Journal of Social Movements, 2024)
This study investigates the social factors contributing to non-compliance among students in salaf-inclusive Islamic boarding schools, with a focus on Al-Munawwir Islamic Boarding School, Komplek L, Bantul, Yogyakarta. Employing a sociological approach, the study collected data through observations, questionnaires, interviews, and literature review, analyzed using data reduction, data display, and interpretation techniques. Triangulation was applied to ensure data credibility. Findings reveal that while most students understand the regulations, the lack of periodic socialization by management contributes to non-compliance. The primary reasons for non-compliance are psychological factors such as laziness, fatigue, and external priorities conflicting with mandatory school hours. A smaller portion of students reported non-compliance due to perceived misalignment between regulations and personal beliefs. Recommendations include strengthening regulation socialization, enhancing time management motivation, and implementing effective sanctions. These findings aim to inform policymakers and contribute to academic discourse on regulation compliance in educational institutions.